Framing Pemberitaan Isu Disabilitas Dalam Media Online Suaramerdeka.com - Nadine Alvira Apny; Nurul Hasfi (Interaksi Online, 2020)
The reporting about the world of disability makes the space of information, insights and intellectuality of the people about the world of disability very inadequate, including in news content that encourages negative stereotypical thinking among the people. Unfavorable treatment of persons with disabilities is experienced not only in actual treatment but also in media texts. The existence of texts that can be detrimental to persons with disabilities is a form of social construction such as text in forms and news texts that place the position of persons with disabilities as disadvantaged parties. Suaramerdeka.com is assumed in its reporting to still not take sides with persons with disabilities as indicated in the debilitating reporting when reporting about disabled street children who are accommodated in Al Rifdah Tlogomulyo's Dual Disability Orphanage, Semarang. Several reports from suaramerdeka.com show that the media cannot be assumed to place persons with disabilities as outsiders. Suaramerdeka.com becomes an interesting media to be investigated in relation to media alignments especially when framing disability issues that can place persons with disabilities as disadvantaged or otherwise disadvantaged parties This study uses analysis of coverage of disability released by the media Suaramerdeka.com. This news analysis uses a framing tool introduced by Zhondang Pan and Gerald Kosicki, which includes syntax, scripts, thematic, and rhetorical. The process of selecting issues and highlighting certain aspects of reality will be known by conducting framing analysis of news framing by the media. The research focused on news that developed from May, June, and July 2019. The results of this study show how suaramerdeka.com framing news of persons with disabilities puts the highlighted party (not disabled) as a strong party. On the other hand, persons with disabilities are often portrayed as opposing parties from the central party in the reporting / the strong. The use of certain terms such as sufferers, disabilities, autism in contexts that are less appropriate for the struggle of persons with disabilities is what marginalizes the position of disability. On the other hand positively, suaramerdeka.com framing people with disabilities as highlighted (important) parties. The use of the term persons with disabilities makes the use of language that is empowered (reinforcing the terms of the disabled persons). There is also a positive side to how suaramerdeka.com conducts framing by placing disabilities as the highlighted party as a strong party. In-depth reporting provides an opportunity for journalists to take sides that benefit persons with disabilities from becoming subject to reporting.